Readability of Online Foot & Ankle Patient Resources. Issue 1 (January 2022) - Cush, Coleman; Foster, Brian; Zhang, Hui; Cush, Gerard J.
Category: Other Introduction/Purpose: The internet is a popular source of health information for patients. Professional organizations, such as the American Orthopaedic Foot & Ankle Society (AOFAS) and the American Academy of Orthopaedic Surgeons (AAOS) have created patient-directed websites containing high quality information. However, previous studies have demonstrated that these sites are often written at a level that is too complex for the average reader. We aimed to investigate the current landscape of the readability of these websites. Methods: Online patient resources on foot and ankle topics published by the AOFAS and AAOS were reviewed. Each page was analyzed using the Flesch Kincaid Grade Level (FKGL) and Flesch Reading Ease (FRE) formulas. Sites were noted if they were written at or below an 8th grade reading level, which corresponds to the average US reading level. An independent two-sample t- test or chi-square test, where appropriate, were used to compare resource characteristics between the two professional societies. Results: 162 total sites were reviewed, including 113 from the AOFAS and 49 from the AAOS. Overall, the mean FKGL was 9.4 (range, 6.7 - 15.3) and the mean FRE was 56.3 (range, 24.4 - 73.1). Websites written by the AAOS had significantly lower FKGL scores than sites written by the AOFAS (9.0 vs 9.5, p=0.01). 31.3% of all sites were written at or below an 8th grade reading level. Websites published by the AAOS had significantly more sites published at this level than sites published by the AOFAS (44.9% vs 25.7%, p=0.02). Conclusion: Online patient information on foot and ankle topics published by professional organizations are often written at a level that is too complex for the average reader. There was a statistical but not clinically significant difference between sites published by the AAOS and AOFAS. Professional organizations should continue to develop their online patient resources, with emphasis on increasing their readability.